2014
DOI: 10.1039/c4ra08214a
|View full text |Cite
|
Sign up to set email alerts
|

New low band gap 2-(4-(trifluoromethyl)phenyl)-1H-benzo[d]imidazole and benzo[1,2-c;4,5-c′]bis[1,2,5]thiadiazole based conjugated polymers for organic photovoltaics

Abstract: Novel low band gap conjugated polymers (PBDTTBIandPBDTBBT) are designed and synthesized for polymer solar cell applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…[ 54‐57 ] The aforesaid calculations were implemented for a single repeating monomeric unit of the polymeric materials VPPy 1‐3 , and to further simplify our calculations, the long alkyl groups were substituted with methyl groups. [ 58 ] The optimized geometries of the single monomeric units of the VPPy 1‐3 , as obtained from their simulations are presented in Figure 8, along with electron density delocalization at their HOMO‐LUMOs and their obtained data are tabulated in Table 3. As got from the results, the HOMOs of polymeric materials VPPy 1‐3 are −6.13 eV ( VPPy 1 ), −5.37 eV ( VPPy 2 ), and −5.47 eV ( VPPy 3 ); whereas their LUMOs are −2.44 eV ( VPPy 1 ), −2.04 eV ( VPPy 2 ), and −2.14 eV ( VPPy 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 54‐57 ] The aforesaid calculations were implemented for a single repeating monomeric unit of the polymeric materials VPPy 1‐3 , and to further simplify our calculations, the long alkyl groups were substituted with methyl groups. [ 58 ] The optimized geometries of the single monomeric units of the VPPy 1‐3 , as obtained from their simulations are presented in Figure 8, along with electron density delocalization at their HOMO‐LUMOs and their obtained data are tabulated in Table 3. As got from the results, the HOMOs of polymeric materials VPPy 1‐3 are −6.13 eV ( VPPy 1 ), −5.37 eV ( VPPy 2 ), and −5.47 eV ( VPPy 3 ); whereas their LUMOs are −2.44 eV ( VPPy 1 ), −2.04 eV ( VPPy 2 ), and −2.14 eV ( VPPy 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the electron density distributions in the FMOs energies, DFT simulations were performed for all the polymers using Turbomole 7.2V software at the B3LYP/TZVP level 46‐49 . The calculations were performed for Py 1‐4 , considering only a single repeating monomeric unit of polymers and further to simplify the calculations, all the solubilizing alkyl groups were substituted with methyl groups 50 . The molecular geometries of a single repeating monomeric unit of polymers were first optimized with semi empirical AM1/COSMO basis using MOPAC in Tmolex 51,52 .…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48][49] The calculations were performed for Py 1-4 , considering only a single repeating monomeric unit of polymers and further to simplify the calculations, all the solubilizing alkyl groups were substituted with methyl groups. 50 The molecular geometries of a single repeating monomeric unit of polymers were first optimized with semi empirical AM1/COSMO basis using MOPAC in Tmolex. 51,52 The obtained molecular geometries of the repetitive unit of the Py 1-4, as optimized from their computation studies are displayed in Figure 5, along with electron cloud distributions in their HOMO-LUMO energies.…”
Section: Theoretical Simulationsmentioning
confidence: 99%
“…Apart from the F atom, other strong electron‐withdrawing moieties such as sulfonyl (SO 2 ), trifluoromethyl (CF 3 ), and cyano (CN) can be incorporated into the structure of conjugated polymers to achieve noticeable improvements in the photovoltaic properties of PSCs . In particular, the CF 3 group has received considerable interest, because it not only possesses higher electron‐withdrawing capability than the F atom but also enables facile tuning of important properties including chemical stability, thermal stability, and solubility . The electronic contributions of the substituents can be expressed by their Hammett constants (σ); the corresponding values for CF 3 and F on the meta ‐position (σ p ) of benzene were calculated as 0.43 and 0.34, respectively .…”
mentioning
confidence: 99%
“…reported that CF 3 groups on the electron‐donating triphenylamine moiety in a D–A polymer can increase the V oc of the PSC up to 1.00 V . In addition, several D–A polymers with CF 3 groups on the electron‐withdrawing components have been prepared for photovoltaic applications . However, the PCEs of these CF 3 ‐containing D–A type polymers have remained less than 1.5% so far.…”
mentioning
confidence: 99%